Partial Amino Acid Metabolism and Glutamine Synthesis as the Ammonia Defensive Strategies During Aerial Exposure in Chinese Loach Paramisgurnus dabryanus - Zhang, Yun-Long; Wang, Guang-Yi; Zhang, Zi-Han; Xie, Yun-Yi; Jin, Hui; Dong, Zhao-Ran (Frontiers in Physiology, 2019)
The Paramisgurnus dabryanus was exposed to air to assess the changes in plasma, liver and muscle free amino acid (FAA) contents. The FAA concentrations in plasma, liver and muscle of P. dabryanus were significantly affected by aerial exposure (P < 0.05). After 12 h of aerial exposure, the plasma glutamate contents increased significantly (P < 0.05) and reached peak value at 24 h of air exposure. With increasing air exposure time, the plasma alanine contents increased significantly and more dramatically than the control values (P < 0.05). From 24 to 48 h of aerial exposure, the liver free glutamate contents increased significantly and reached the peak value at 48 h of air exposure (P < 0.05). The liver free alanine contents in air exposure group were markedly higher than these values in the control group (P < 0.05). After 72 h of air exposure, the muscle free glutamate contents increased markedly (P < 0.05) and were significantly higher than the control values (P < 0.05). The muscle free alanine contents remained at constant values during the first 12 h of aerial exposure (P > 0.05), thereafter, these concentrations increased significantly until the end of experiment (P < 0.05). Our results showed that glutamate and NH4+ could be used to synthesize glutamine via glutamine synthetase to convert internal ammonia into non-toxic glutamine in P. dabryanus during air exposure. Furthermore, the P. dabryanus could catabolize several certain amino acids, leading alanine form to reduce endogenous ammonia production. The decrease in tissue free glutamate, arginine and proline in P. dabryanus indicated that these certain amino acids should be the starting substrate to be converted to alanine and energy.